Absence of Foxp3+ Regulatory T Cells during Allergen Provocation Does Not Exacerbate Murine Allergic Airway Inflammation - Baru, Abdul Mannan; Ganesh, Venkateswaran; Krishnaswamy, Jayendra Kumar; Hesse, Christina; Untucht, Christopher; Glage, Silke; Behrens, Georg; Mayer, Christian Thomas; Puttur, Franz; Sparwasser, Tim (PLOS ONE, 2012)
Regulatory T cells (Tregs) play a non-redundant role in maintenance of immune homeostasis. This is achieved by suppressing both, priming of naïve cells and effector cell functions. Although Tregs have been implicated in modulating allergic immune responses, their influence on distinct phases of development of allergies remains unclear. In this study, by using bacterial artificial chromosome (BAC)-transgenic Foxp3-DTR (DEREG) mice we demonstrate that the absence of Foxp3+ Tregs during the allergen challenge surprisingly does not exacerbate allergic airway inflammation in BALB/c mice. As genetic disposition due to strain specificity may contribute significantly to development of allergies, we performed similar experiment in C57BL/6 mice, which are less susceptible to allergy in the model of sensitization used in this study. We report that the genetic background does not influence the consequence of this depletion regimen. These results signify the temporal regulation exerted by Foxp3+ Tregs in limiting allergic airway inflammation and may influence their application as potential therapeutics.